A SYSTEMATIC REVIEW: RISK FACTOR FOR BURNOUT-INDUCED HYPERTENSION AMONG WORKERS - Rezky Amelia Putri; Solikhah Solikhah; Sulistyowati Sulistyowati (Insights in Public Health Journal, 2025)
Background : Burnout can be described as a state of physical and psychological exhaustion from job demands or pressures at work that make a person experience prolonged stress. Purpose : This study conducted a systematic review of risk factors for burnout-induced hypertension among workers. Methods: The system review design with PICO and PRISMA flowchart was used; articles were selected from PubMed, ScienceDirect, and inclusion criteria were articles that had risk ratio and relative risk values in case-control or cohort studies. Results: This study analyzed 5 articles and found that chronic work stress can show chronic work stress increases the risk of metabolic syndrome (OR 2.25), no significant association between fatigue and hypertension (OR 0.62), moderate (OR 19.72) and severe (OR 32.55) stress increases the risk of hypertension, fatigue increases the risk of heart attack (RR 2.13). Conclusions: Burnout increases the risk of hypertension among workers. It is important for workers and companies to pay attention to the signs of fatigue and take appropriate precautions to keep their hearts healthy.